2016
DOI: 10.1007/s00192-016-3050-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-face-to-face treatment of stress urinary incontinence: predictors of success after 1 year

Abstract: Introduction and hypothesisThe objective was to determine predictors of long-term success in women with stress urinary incontinence (SUI) treated with a 3-month pelvic floor muscle training (PFMT) program delivered via the Internet or a brochure.MethodsWe included 169 women with SUI ≥1 time/week who completed the 1-year follow-up (n = 169, mean age 50.3, SD 10.1 years). Three outcome variables defined success after 1 year: Patient Global Impression of Improvement (PGI-I), International Consultation on Incontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
7
32
1
Order By: Relevance
“…Another possible explanation is self-efficacy. Self-assessed ability to carry out PFMT predicts long-term success [ 15 ], but has not been evaluated in other studies of predictors. The benefit of high educational level found in other studies [ 14 ] and the influence of expectations for treatment found in our study could both be surrogate measures of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another possible explanation is self-efficacy. Self-assessed ability to carry out PFMT predicts long-term success [ 15 ], but has not been evaluated in other studies of predictors. The benefit of high educational level found in other studies [ 14 ] and the influence of expectations for treatment found in our study could both be surrogate measures of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these results, poor contraction at baseline predicted success in one other study of PFMT and bladder training [ 25 ]. From other reports, we know that short-term results predict long-term outcomes [ 15 , 26 ]. The participants in our study received the app-based treatment without any physical examination or face-to-face care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samuelsson et al presented a smartphone application as an easily accessible, cost effective treatment for stress urinary incontinence (SUI) and they were awarded joint winner of the Conservative Management Award. Given that many are still smartphone illiterate and 40% perform pelvic floor exercises incorrectly this application can provide an adjunct to, rather than replace, individualized pelvic floor training with digital palpation (Abstracts 16, 521, 526).…”
Section: Introductionmentioning
confidence: 99%